2015
DOI: 10.1186/s12931-015-0224-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction via TRPV4 regulates inflammation and differentiation in fetal mouse distal lung epithelial cells

Abstract: BackgroundMechanical ventilation plays a central role in the injury of premature lungs. However, the mechanisms by which mechanical signals trigger an inflammatory cascade to promote lung injury are not well-characterized. Transient receptor potential vanilloid 4 (TRPV4), a calcium-permeable mechanoreceptor channel has been shown to be a major determinant of ventilator-induced acute lung injury in adult models. However, the role of these channels as modulators of inflammation in immature lungs is unknown. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…TRPV4 is expressed in adult lung [10,11,12]; however, whether undifferentiated distal epithelial cells express TRPV4 and the response to mechanical injury were unknown. Recent studies from our laboratory have found that TRPV4 is expressed in the fetal lung, and specifically in the bronchial and distal epithelium [13]. Moreover, in vitro experiments in isolated distal epithelial cells found that TRPV4 expression level responded to mechanical signals.…”
Section: +mentioning
confidence: 87%
See 2 more Smart Citations
“…TRPV4 is expressed in adult lung [10,11,12]; however, whether undifferentiated distal epithelial cells express TRPV4 and the response to mechanical injury were unknown. Recent studies from our laboratory have found that TRPV4 is expressed in the fetal lung, and specifically in the bronchial and distal epithelium [13]. Moreover, in vitro experiments in isolated distal epithelial cells found that TRPV4 expression level responded to mechanical signals.…”
Section: +mentioning
confidence: 87%
“…Moreover, in vitro experiments in isolated distal epithelial cells found that TRPV4 expression level responded to mechanical signals. This response was gestational-age dependent, being the canalicular stage of lung development the period of gestation more sensitive to mechanical injury [13].…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…This produces a range of IL-6 change that not only changes continuously from the activation of the TRPM8 receptor at 8°C but also continues in a downward trend until the peak activity of TRPV4. 1,3 Additionally, this corresponds roughly to the range of Clostridium perfringens germination activity, which peaks roughly around 44°C in a growth curve. 4 Clostridium perfringens is a bacteria known for cold related conditions such as gangrene.…”
Section: Introductionmentioning
confidence: 96%
“…Due to its expression in the adult lung, TRPV4 has been implicated in mediating the mechanosensitive response to ventilator-induced barotrauma 22,23 . While this response has been minimally investigated in late fetal lungs 49 , TRPV4’s direct correlation to early lung development remains unstudied.…”
Section: Introductionmentioning
confidence: 99%